Novel Anticancer Strategies (Volume II) - Bousbaa, Hassan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Novel Anticancer Strategies (Volume II) reviews important findings and updates within the cancer therapy field of great interest to those in academic research studying the development and validation of novel anticancer approaches. The Editor invited preeminent specialists to contribute to original and review articles devoted to key areas of major progress and expectations. Key Features:Nanoparticle-based drug delivery in cancer therapy;Nanoerythrosomes;Cancer immunotherapy;Therapeutic vaccines;Oncogenic and tumor suppressive components of the cell cycle;Antimitotics in cancer clinical trials;Multifunctional enzymes as anti-cancer drug targets;Targeting undruggable proteins and non-coding RNAs;Cell-penetrating peptides;Repurposed cancer drugs in clinical trials;Circulating tumour cells.